Neuronal Polarity in the Embryonic Mammalian Cerebral Cortex - Kon, Elif; Cossard, Alexia; Jossin, Yves (Frontiers in Cellular Neuroscience, 2017)
The cerebral cortex is composed of billions of neurons that can grossly be subdivided into two broad classes: inhibitory GABAergic interneurons and excitatory glutamatergic neurons. The majority of cortical neurons in mammals are the excitatory type and they are the main focus of this review. Like many of the cells in multicellular organisms, fully differentiated neurons are both morphologically and functionally polarized. However, they go through several changes in polarity before reaching this final mature differentiated state. Neurons are derived from polarized neuronal progenitor/stem cells and their commitment to neuronal fate is decided by cellular and molecular asymmetry during their last division in the neurogenic zone. They migrate from their birthplace using so-called multipolar migration, during which they switch direction of movement several times, and repolarize for bipolar migration when the axon is specified. Therefore, neurons have to break their previous symmetry, change their morphology and adequately respond to polarizing signals during migration in order to reach the correct position in the cortex and start making connections. Finally, the dendritic tree is elaborated and the axon/dendrite morphological polarity is set. Here we will describe the function, establishment and maintenance of polarity during the different developmental steps starting from neural stem cell division, neuronal migration and axon specification at embryonic developmental stages.